AN ANALYSIS OF VALIDITY AND RELIABILITY OF COGNITIVE TAXONOMY ITEMS ON ENGLISH SUMMATIVE TEST AT SMA NURUL FALAH PEKANBARU - Sianturi, Murni Wahyuni; Erni, Erni; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aimed to analyze the quality of summative test that wasconducted by the teacher at the eleventh grade of SMA Nurul Pekanbaru and wasconstructed as descriptive quantitative research. The sample consisted of 53 students inthe second semester of the academic year 2020/2021 and was selected by using totalsampling with the lottery method. Furthermore, the instrument of English final test thatconstructed in the form of 40 multiple choice questions was firstly identified andgrouped based on the classification of each domain of cognitive dimension according toBloom’s taxonomy revision that contained two levels namely HOTS (High OrderThinking Skills) and LOTS (Low Order Thinking Skills). Then, all students’ answerswere analyzed by using SPSS (Statistical Package for the Social Sciences) version 25for windows to analyze the validity and reliability of the test. The result showed that thetest questions just obtained 50% of applying (C3), 27.5% of understanding (C2), and22.5% of remembering (C1) of LOTS levels whereas HOTS levels (analyzing,evaluating, and creating) weren’t even found. Furthermore, its reliability quotient wasjust 0.729 (lower than 1.00) with 3 (8%) items categorized as invalid questions, and thevalid items of 37 (92%) questions were predominantly classified in low interpretation.This research clearly showed that the test didn’t fulfill the qualification of a good test.Key Words: Validity, Reliability, Cognitive, Educational Taxonomies, Summative Test